The Mutations and Clinical Variability in Maternally Inherited Diabetes and Deafness: An Analysis of 161 Patients - Yang, Mengge; Xu, Lusi; Xu, Chunmei; Cui, Yuying; Jiang, Shan; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2021)
Aims: To investigate the clinical features and mitochondrial mutations for maternally inherited diabetes and deafness. Methods: PubMed, Embase, Medline, Web of Science, the China National Knowledge Infrastructure, and Wanfang were searched with the following search terms: ‘Maternally inherited diabetes and deafness’ OR ‘MIDD’ OR ‘Mitochondrial diabetes’. The mutations and clinical features were analyzed. Correlation between the heteroplasmy levels of the m.3243A>G mutation in the peripheral blood and age at the onset of diabetes was conducted by Spearman test. The significance level was set as p < 0.05. Statistical analysis was performed using the Statistical Package for the Social Sciences version 26 for Windows. Results: Totally 161 patients with 21 different mitochondrial mutations were enrolled. The most common mutation was the m.3243A>G mutation in 136 cases. 84.51% (120/142) of the patients had family histories of diabetes or hearing loss. Hearing loss presented in 85.71% of the patients with mitochondrial mutations. Central nervous system diseases were found in 29.19%, myopathy in 22.98%, oculopathy in 23.60%, cardiac disease in 23.60%, and nephropathy in 13.66% of the patients. 41.58% (42/101) of the patients were underweight. A significant negative correlation was found between the heteroplasmy levels of the m.3243A>G mutation in the peripheral blood and age at the onset of diabetes. Conclusions: The young onset of diabetes with low or normal BMI, maternal inheritance and presence of impairments of multiple systems should prompt a genetic testing in order to differentiate MIDD from other types of diabetes earlier.